Assessment of a cylindrical porous radiant burner with internal combustion regime for sustainable energy: Numerical analysis of the radiant efficiency and NO production. (February 2021) - Vahidhosseini, Seyed Mohammad; Esfahani, Javad Abolfazli; Kim, Kyung Chun
Abstract: A numerical assessment is conducted on a premixed axisymmetric two-dimensional porous radiant burner. Equations of continuity, momentum, energy, turbulence, radiation, progress variable, and mixture fraction are solved using a structured grid with a high degree of accuracy. A good agreement between the results and the available data are observed. The flame cannot pass through the thin porous medium and increases the solid phase temperature, consequently, leads to an increase in radiant efficiency. Temperature contours represent very low temperature for burner exhaust gases, leading to decrease in the energy losses. The effects of three parameters of input power, equivalence ratio, and porosity on radiant efficiency and NO production rate are investigated. Due to the number of parameters studied, the validated numerical solutions can prevent spending extra time and money to produce porous mediums with different properties, and therefore, the operating conditions can be analyzed from environmental and energy saving points of view. A radiant efficiency of above 50% is achieved. In addition, it is concluded that there is an optimum equivalence ratio lower than unity, about 0.83 at P, ε p = 4.938 k W, 0.65, which maximizes the radiant efficiency. Furthermore, the results indicate that the NO production rate increases by increasing the input power/equivalence ratio.